Digital Literacy and ICT-Based Supervision: Antecedents of Work Discipline in Coastal Public Sector Organizations - Shalahuddin Shalahuddin; Aswan Aswan; Ahmad Shakani Abdullah; Mohd Noor Hidayat Jimainal; Nor Afifah Yusof (LPPM STIE KRAKATAU, 2025)
Purpose: This study aimed to examine the effect of ICT-based supervision on employee work discipline and to analyze the moderating role of digital literacy in public sector organizations in coastal areas. Methodology: A quantitative approach was employed using survey data collected from 217 public sector employees. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. Results: The results showed that ICT-based supervision had a positive and significant effect on work discipline. Digital literacy also had a strong and significant influence and emerged as the most dominant factor. However, the moderating effect of digital literacy was not statistically significant. Conclusions: The findings indicated that human capability, particularly digital literacy, played a more critical role than technological systems in shaping employee discipline. Limitations: This study was limited by its cross-sectional design and focus on a specific regional context, which may affect generalizability. Contributions: This study contributed to digital governance literature by highlighting the dominant role of digital literacy and providing empirical evidence from coastal regions.